DEVELOPMENT OF PARAMETER PREDICTION MODELS FOR PREDICTING THE STAND CHARACTERISTICS OF ACACIA MANGIUM PLANTATIONS - Abd Kudus, Kamziah; Ahmad, M; Lapongan, Jaffirin (วารสารวนศาสตร์ไทย, 2022)
A procedure for predicting diameter distribution of Acacia mangium plantations was developed based on the univariate So distribution model. In simulation of stand characteristics, equations were developed for predicting average height, basal area per hectare, and number of trees per hectare surviving when age, spacing and number of trees per hectare planted were known. The predicted stand characteristics were then related to the estimated parameters of the Johnson Sp and solving the resulting set of equations for the scale and shape parameters. This study revealed that the parameter prediction method yields reliable prediction equations of the stand characteristics, but the prediction equations of the scale and shape parameters suggested that further research is needed to improve the model